Economic efficiency of water storage options: an application of the approach to Ghana - Xenarios, Stefanos; Asante, F.; McCartney, Matthew P. (2011)
Water storage is widely promoted as an effective method for mitigating some of the adverse impacts of climate change. Cost benefit analysis is one approach to evaluate which is the most appropriate water storage type under any specific biophysical and socio-economic conditions. However, this often result in loss of significant information for those characteristics which cannot be easily assessed using monetary values. Against this background, the study reported in this paper developed an outranking-based methodology, designed with threshold systems and weighting values, in order to overcome some of the constraints of traditional cost-benefit analysis. The method has been applied in three representative catchments in central and northern Ghana. The results present a preponderance of upstream areas linked with small reservoirs because of the considerably high income, the sufficient water supply, the low costs given for water related illnesses and the low costs for domestic water use.